Defoliants and Desiccants - Joseph E. Iboyi; Michael J. Mulvaney; Mahesh Bashyal; Pratap Devkota; David L. Wright (EDIS)
This document discusses the meaning of the terms “defoliant” and “desiccant,” their uses, and factors that impact their performance, and also provides a list of registered products for use in Florida. Written by Joseph E. Iboyi, Michael J. Mulvaney, Mahesh Bashyal, Pratap Devkota, and David L. Wright, and published by the UF/IFAS Agronomy Department, revised November 2021.